Beyond quantifier-free interpolation in extensions of presburger arithmetic - Brillout, A; Kroening, D; Rümmer, P; Wahl, T (Springer, 2011)
Craig interpolation has emerged as an effective means of generating candidate program invariants. We present interpolation procedures for the theories of Presburger arithmetic combined with (i) uninterpreted predicates (QPA+UP), (ii) uninterpreted functions (QPA+UF) and (iii) extensional arrays (QPA+AR). We prove that none of these combinations can be effectively interpolated without the use of quantifiers, even if the input formulae are quantifier-free. We go on to identify fragments of QPA+UP and QPA+UF with restricted forms of guarded quantification that are closed under interpolation. Formulae in these fragments can easily be mapped to quantifier-free expressions with integer division. For QPA+AR, we formulate a sound interpolation procedure that potentially produces interpolants with unrestricted quantifiers.